The influence of ageing on martensite morphology in shape memory CuZnAl alloys - Kayali, N; Ozgen, S; Adiguzel, O (E D P Sciences, 1997)
The martensitic transformation behaviour, morphology and microstructures in copper-based shape memory alloys are strongly influenced by the post-quench heat treatments and ageing. Martensitic transformation initiates at a critical temperature and grows by the formation of martensite variants on cooling up to martensite finish temperature. These alloys are metastable at the matrix beta-phase condition, and reversibility of transformation and formation of martensite variants from the matrix are related to the elementary mechanisms. ?The interfacial motion between martensite variants is also important in shape memory. Vickers hardness shows a trend to increase with holding duration at ageing temperature of 200 degrees C for both alloys. Martensite plates have similar morphology in as-quenched and post-quench heat treated specimens, and growth units of two or four plates constitute self-accommodating systems.
European Symposium on Martensitic Transformations (ESOMAT 97) -- JUL 01-05, 1997 -- UNIV TWENTE, ENSCHEDE, NETHERLANDS
Keywords: Stabilization; Transformation; Behavior